2012
DOI: 10.5402/2012/730862
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Durable High-Strength Flowable Mortar Reinforced with Hybrid Fibers

Abstract: The production and use of durable materials in construction are considered as one of the most challenging things for the professional engineers. Therefore, this research was conducted to investigate the mechanical properties and the durability by using of different percentages of steel fiber with high-strength flowable mortar (HSFM) and also the use of the hybridization of steel fibers, palm fibers, and synthetic fiber (Barchip). Different experimental tests (compressive strength, splitting tensile strength, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In comparative research on MSF-reinforced cement mortar ( 24 ), the authors used 2% MSF with an aspect ratio of 54 to reinforce cement mortar, whereas the average aspect ratio of the RSF used in this study is 55. Therefore, the fiber dimensions are similar between the two studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparative research on MSF-reinforced cement mortar ( 24 ), the authors used 2% MSF with an aspect ratio of 54 to reinforce cement mortar, whereas the average aspect ratio of the RSF used in this study is 55. Therefore, the fiber dimensions are similar between the two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Transportation Research Record 2674 (8) rubber in the studied RSF did not seem to negatively influence the properties of the cement mortars, though it has been found that rubber could lead to incomplete cement hydration (14) and yield a weaker interfacial transition zone (15). In comparative research on MSF-reinforced cement mortar (24), the authors used 2% MSF with an aspect ratio of 54 to reinforce cement mortar, whereas the average aspect ratio of the RSF used in this study is 55. Therefore, the fiber dimensions are similar between the two studies.…”
mentioning
confidence: 82%